The Boo of Viramontes’s Cafe: Retelling Ghost Stories, Central American Representing Social Death - Karina Oliva Alvarado (Studies in 20th & 21st Century Literature, 2013)
Chicana author Helena María Viramontes’s culturally complex “The Cariboo Cafe,” renders a contemporaneous example of social death in the lives of undocumented migrants. Sociologist Orlando Patterson bases “social death” on the “profound natal alienation of the slave” (38) that once cut off from a past and future, promulgates the slave’s desocialization and depersonalization: systems also at play with undocumented Central American immigrants. While Patterson refers to an overt and systemized economic exploitation of a people, the concept remains relevant to this analysis, though symbolic. It examines a three-fold negation through the representational experiences of undocumented immigration, gender, and what Arturo Arias calls Central American “nonentity” (186), in Viramontes’s short story to address Central American differences erased by the utopian desire for reconciliation in Chicana/Latina texts. While social death is originally conceived and applied through “a mode of oppression through which slaves, and by extension those who grew up under the control of Jim Crow society” were coerced through hegemony (JanMohammed 246), its current relevance is allegorical to the conditions that delocalized and depersonalized literary representations of Central Americans. The question is what contemporary hegemonies socially kill the articulation of Central American subjectivities in a Latina/o US imaginary.
Keywords: Chicano/a; Chicana author; Helena María Viramonte; The Cariboo Cafe; migrants; undocumented migrants; social death; immigrants; Chicana/Latina texts; oppression; slavery; hegemony